"How I whiten my teeth": YouTube™ as a patient information resource for teeth whitening - Huseyin Simsek; Suleyman Kutalmış Buyuk; Ebru Cetinkaya; Mubin Tural; Murside Seda Koseoglu (BMC, 2020)
Abstract Background YouTube™ is the world's second most popular website after Google on the Internet. The aim of this study was to assess the quality and content of information YouTube™ videos for patients seeking information about teeth whitening. Methods The keyword 'teeth whitening' was searched on YouTube™. YouTube™ was filtered by the relevance, and the first 100 videos that met the inclusion criteria were evaluated. The included videos were analyzed for views, duration, time since video upload, likes/dislikes, number of comments, source, material types (dental, natural, and other). Also, video purpose was analyzed under nine categories (definition, material preparation, the procedure of application, material comparison, before/after comparison, symptoms, post-op experience, commercial, educational). Each video was classified according to the quality of information content as 'good', 'moderate', or 'poor'. The Kruskal-Wallis test, Fischer's Exact test and Spearman correlation analyses were performed. Results Most videos were uploaded by laypersons (60.0%). The definition of teeth whitening was the most commonly covered topic (74.0%), followed by the procedure of application (54.0%), and post-op experience (36.0%). Only 12% of videos were classified as having good information quality content, 53% moderate, and 35% were rated as poor information content. Poor-information content videos had a significantly higher number of viewing rates than the other groups (P = 0.002), besides the duration was significantly higher in poor-information content videos (P =0.002). There was a significant relationship between the quality of video information and material types (P <0.001). Conclusions YouTube™ should not be used as a thoroughly reliable and accurate source for patient information about teeth whitening. More informative and reliable content YouTube™ videos about teeth whitening should be uploaded by professionals.